Penguatan Daya Saing UMKM dengan Strategi Branding melalui Digital Marketing dan Desain Visual: Implementasi Program KKM-PKM - Putri, Dea Avilla; Ramadhan, Rizani; Anjelani, Ratu; Lidiya, Lidiya; Syarini, Syarini; Lastri, Putri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Micro, Small, and Medium Enterprises (UMKM) in Indonesia, particularly in Pulau Tayan Barat Village, face challenges in competing in an increasingly competitive market, especially related to branding and marketing. Many UMKM in the village still rely on traditional promotion methods such as banners, which have limited reach, and lack knowledge in using digital media as a more effective promotional tool. This article aims to help UMKM enhance their competitiveness by optimizing branding through training and mentoring in utilizing digital marketing and visual design. The method used involves training on branding concepts, designing attractive banners, and using social media for promotion. The results of this activity show that UMKM actors in Pulau Tayan Barat Village are becoming more aware of the importance of strong branding in building business image and are gaining skills in managing digital media and brand visualization. In conclusion, the synergy between using banners and social media can help increase the visibility of UMKM, where social media offers a wider market reach, while banners remain important for attracting local attention if designed and placed properly.